KONTROVERSI PERNYATAAN BAHLIL DAN SRI MULYANI TERKAIT GAS LPG 3 KG - Natanael Tristyanto; Mayasari; Ema (Halu Oleo University, 2025)
The statements made by Bahlil and Sri Mulyani regarding 3 kg of LPG gas have sparked public controversy. These statements were disseminated through Kompas.com's YouTube channel and Sri Mulyani's Instagram account, @Smindrawati. This research aims to analyse the statements of Bahlil and Sri Mulyani on 3 kg LPG gas through the dimensions of text, discourse practice, and socio-culture. A qualitative method with Norman Fairclough's Critical Discourse Analysis model was used. The research findings on the textual dimension show linguistic aspects of diction, modality, cohesion, and coherence that represent identity and power relations. The discourse practice reveals the production of texts by Bahlil and Sri Mulyani, which were disseminated via Kompas.com's YouTube channel and Sri Mulyani's Instagram account, @Smindrawati. These texts were consumed predominantly by the lower-class community. The socio-cultural dimension outside the text indicates the influence of social egalitarianism in the formation of the discourse, which represents an effort to maintain the current government's power.